Natural human rights : a theory - Boylan, Michael, 1952- (Cambridge : Cambridge University Press, 2014)
This timely book by internationally regarded scholar of ethics and social/political philosophy, Michael Boylan, focuses on the history, application and significance of human rights in the West and China. Boylan engages the key current philosophical debates prevalent in human rights discourse today and draws them together to argue for the existence of natural, universal human rights. Arguing against the grain of mainstream philosophical beliefs, Boylan asserts that there is continuity between human rights and natural law and that human beings require basic, essential goods for minimum action. These include food, clean water and sanitation, clothing, shelter and protection from bodily harm, including basic healthcare. The achievement of this goal, Boylan demonstrates, will require significant resource allocation and creative methods of implementation involving public and private institutions. Combining technical argument with four fictional narratives about human rights, the book invites readers to engage with the most important aspects of the discipline.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Human rights -- Philosophy; Human rights -- Cross-cultural studies; Natural law; Natural law -- Philosophy